Distributed fault detection for interconnected large-scale systems: a scalable plug & play approach - Boem,F; Carli,R; Farina,M; Ferrari-Trecate,G; Parisini,T (IEEE Transactions on Control of Network Systems, 2019)
In this paper, we propose a novel distributed fault detection method to monitor the state of a - possibly large-scale - linear system, partitioned into interconnected subsystems. The approach hinges on the definition of a partition-based distributed Luenberger-like estimator, based on the local model of the subsystems and that takes into account the dynamic coupling between the subsystems. The proposed methodology computes - in a distributed way - a bound on the variance of a properly defined residual signal. This bound depends on the uncertainty affecting the state estimates computed by the neighboring subsystems and it allows the computation of local fault detection thresholds, as well as the maximum false-alarms rate. The implementation of the proposed estimation and fault detection method is scalable, allowing Plug & Play operations and the possibility to disconnect the faulty subsystem after fault detection. Theoretical conditions on the convergence properties of the estimates and of the estimation error bounds are provided. Simulation results on a power network benchmark show the effectiveness of the proposed method.